1992
DOI: 10.1002/1098-108x(199211)12:3<291::aid-eat2260120309>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Body images, body-size perceptions, and eating behaviors among African-American and white college women

Abstract: Previous research indicates a lower prevalence of eating disorders within black than white populations. The purpose of this investigation was to examine multiple facets of body image and eating behaviors among 104 African‐American and white female college students. Four primary domains assessed in this study were: (a) body‐image attitudes, (b) body‐image perceptions, (c) weight concerns and eating behaviors, and (d) judgments of the thinness‐fatness of varying body sizes. As hypothesized, black females held mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
233
5
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 368 publications
(252 citation statements)
references
References 35 publications
12
233
5
2
Order By: Relevance
“…For example, higher rates of such behaviours have been found in white women when compared to black andaor Asian women, in terms of bulimic behaviours, 1 generalised disordered eating 2,3 and body dissatisfaction and eating concerns. 4,5 However, in direct contrast, other studies report the reverse relationship between ethnicity and weight concern. For example, Mumford et al 6 reported results from a school in the north of England which indicated that the prevalence of bulimia nervosa was higher amongst Asian schoolgirls than their white counterparts.…”
Section: Introductionsupporting
confidence: 75%
“…For example, higher rates of such behaviours have been found in white women when compared to black andaor Asian women, in terms of bulimic behaviours, 1 generalised disordered eating 2,3 and body dissatisfaction and eating concerns. 4,5 However, in direct contrast, other studies report the reverse relationship between ethnicity and weight concern. For example, Mumford et al 6 reported results from a school in the north of England which indicated that the prevalence of bulimia nervosa was higher amongst Asian schoolgirls than their white counterparts.…”
Section: Introductionsupporting
confidence: 75%
“…On the one hand, adults in their achievement-oriented communities strongly emphasize excellence at school, and on the other hand the media, and often the peer group, convey powerful messages that to display high intelligence or academic competence is "non-feminine" and thus undesirable. Additional stressors may derive from high concern with personal appearance (Luthar & Feldman, 1999;Pipher, 1994), as preoccupation and dissatisfaction with their physical appearance tend to be particularly pronounced among young Caucasian women (Abrams, Allen, & Gray, 1993;Cash & Henry, 1995;Rodin, Silberstein, & Striegel-Moore, 1984;Rucker & Cash, 1992). In future research, there is clearly a need for systematic inquiry into the diverse sources of stress that are potentially unique to this subgroup of adolescent girls.…”
Section: Gender Differences In Associationscontrasting
confidence: 50%
“…This is consistent with meanings of body weight and shape in non-western 6 and black 19 women, and with local Zulu custom which has traditionally valued plumpness as a sign of wellbeing; while thinness has been associated with illness, stress or deprivation. Traditional rituals of purging (vomiting and laxative use) were also identified as culturally sanctioned forms of remediation for a wide range of physical and psychological maladies.…”
Section: Discussionmentioning
confidence: 99%